The total money makeover : a proven plan for financial fitness - Ramsey, Dave (Nelson Books, an imprint of Thomas Nelson, 2013)
If you will live like no one else, later you can live like no one else. Build up your money muscles with America's favorite finance coach. Okay, folks, do you want to turn those fat and flabby expenses into a well-toned budget? Do you want to transform your sad and skinny little bank account into a bulked-up cash machine? Then get with the program, people. There's one sure way to whip your finances into shape, and that's with The Total Money Makeover: Classic Edition. By now, you've heard all the nutty get-rich-quick schemes, the fiscal diet fads that leave you with a lot of kooky ideas but not a penny in your pocket. Hey, if you're tired of the lies and sick of the false promises, then take a look at this -- it's the simplest, most straightforward game plan for completely making over your money habits. And it's based on results, not pie-in-the-sky fantasies. With The Total Money Makeover, you'll be able to: Design a surefire plan for paying off all debt -- cars, houses, everything; Recognize the 10 most dangerous money myths (these will kill you); Secure a big, fat nest egg for emergencies and retirement! Where Financial Peace gave you the solid saving and investing principles, this book puts those principles into practice. You'll be exercising your financial strength every day and quickly freeing yourself of worry, stress, and debt -- and that's a beautiful feeling. In the 10 years since it first released, millions of ordinary people have experienced their own Total Money Makeover. What are you waiting for? The Total Money Makeover: Classic Edition -- with timeless wisdom, fresh insights, and new back-of-the-book resources -- is the one financial workout that guarantees everything will work out. - Jacket.